Claves para pensar la formación del hábito lector - Salazar Ayllón, Silvana (2005)
Peru is experiencing an unprecedented social climate of reading. At first glance, this statement seems exaggerated, but there is sufficient evidence that the population is reacting positively to the set of stimuli and efforts -not always structured, but valid- to motivate them towards the exercise of this important activity.